Detection of natural pulse waves (PWs) in 3D using high frame rate imaging for anisotropy characterization - Sauvage, Jack; Moustefaoui, Safa; Fiorentini, Stefano; Venet, Maelys; Fadnes, Solveig; Lovastakken, Lasse; Villemain, Olivier; Salles, Sébastien (Frontiers in Physics, 2024)
Numerous studies have shown that natural mechanical waves have the potential to assess the elastic properties of the myocardium. When the Aortic and Mitral valves close, a shear wave is produced, which provides insights into tissue stiffness. In addition, the Atrial Kick (AK) generates a wave similar to Pulse Waves (PWs) in arteries, providing another way to assess tissue stiffness. However, tissue anisotropy can also impact PW propagation, which is currently underexplored. This study aims to address this gap by investigating the impact of anisotropy on PW propagation in a phantom. Tube phantoms were created using Polyvinyl Alcohol (PVA). Anisotropy was induced between two sets of two freeze-thaw cycles by stretching and twisting the material. The study first tests and validates the procedure of making an anisotropic vessel phantom using the shear wave imaging technique (by estimating the shear wave speed at different probe angles). Using plane wave ultrasound tomography synchronized with a peristaltic pump, 3D high frame rate imaging is performed and used to detect the 3D propagation pattern of PW for each manufactured vessel phantom. Finally, the study attempts to extract the anisotropic coefficient of the vessel using pulse wave propagation. The results show that anisotropy can be induced in PVA vessel phantoms by stretching and twisting. As well known for other tissues, such as the myocardium, the findings also suggest that vessel anisotropy affects pulse wave propagation. Finally, as a potential method for extracting vessel anisotropy, we propose an anisotropy coefficient that reflects the number of circumferential turns during vessel fabrication.